A generic measurement model for system data definition and database requirements. (2013) - Al-Khasawneh, Ahmad; Al-Sarayreh, Khalid T.; Meridji, Kenza; Khasawneh, Mohammad
Data definition and database requirements are considered one of the 16 types of Non-Functional Requirements (NFRs) for embedded and real-time software at the system level, which may lead to specific reference database models and standard data definitions. According to ECSS standards series, a reference model for a standard data definition and database requirement could be defined by the data requirements and the corresponding mission data provided by a supplier to a customer. A number of concepts and terms are provided to describe various types of candidate system model objects, which are composed of the data model requirements and data mission. This paper organises these data definitions and database-related requirements into a generic model of the requirement for software data definition and database; this generic model corresponds to a standard-based framework for modelling software-NFR for data definitions and database. This size may be used next to improve software project estimates.